High cervical commissural myelotomy in the treatment of pain. - Papo, I (1976)
High cervical myelotomy was carried out on 10 patients. Commissurotomy was performed at the C1-3 level by a combined procedure of deep electrocogulation and sharp splitting of the posterior columns. The immediate results were excellent in all patients, but relapse of pain took place shortly in six of them; there was apparently no relation with the location of pain. No long-term favourable results were observed in this series. Only three patients exhibited a well-defined band of mild hypalgesia from C2 to T 10 dermatome, but it lasted for only three to four weeks. Transient lower or four limb ataxia was observed in seven patients. Different pain conducting systems seem to be affected by commissural myelotomy, but not to a sufficient extent to give permanent or long-lasting relief of pain. The indications for high cervical myelotomy are very limited: this procedure should be considered only in patients with unilateral or bilateral arm and/or upper chest pain, respiratory impairment, and short life expectancy.